Trust and the sharing economy - Louise Pelgander; Christina Öberg; Louise Barkenäs (Digital Business, 2022)
Trust is intimately connected with relational interactions, but does it also have a role to play in transactional exchanges? How would it differ? While trust has been discussed extensively in sharing economy research, the focus has been on trust cues created in exchanges between strangers, thereby approaching trust empirically rather than theoretically. Focusing on user trust, this paper investigates how trust constructs from relational interactions manifest in the sharing economy. This paper bridges sharing economy research with trust as a theoretical construct to investigate the well-established variables of ability, benevolence and integrity as components of trust in the sharing economy. The paper is based on a questionnaire survey of 175 users of Uber's co-driving service UberPop. Descriptive and regression analyses were conducted focusing on user trust in the platform and providers. The findings indicate how trust in transactional exchanges is shaped differently compared with trust in relational interactions. User trust in providers, which diminishes over time, is based on emotional traits, while user trust in the platform is based on functional components. The platform and providers thereby complement each other in terms of the trust created. This paper contributes to research on trust by focusing on trust in transactional exchanges, and to research on the sharing economy by investigating trust based on theoretical constructs.
Keywords: 650; Co-riding; Literature review; Sharing economy; SurveyTrust